Supersymmetric Born-Infeld from the pure spinor formalism of the open superstring - Berkovits, Nathan [UNESP]; Pershin, Vladimir [UNESP] (Springer Nature, 2003)
Classical BRST invariance in the pure spinor formalism for the open superstring is shown to imply the supersymmetric Born-Infeld equations of motion for the background fields. These equations are obtained by requiring that the left and right-moving BRST currents are equal on the worldsheet boundary in the presence of the background. The Born-Infeld equations are expressed in N = 1 D = 10 superspace and include all abelian contributions to the low-energy equations of motion, as well as the leading non-abelian contributions. © SISSA/ISAS 2003.
Keywords: D-branes; Extended Supersymmetry; Superstrings and Heterotic Strings